Aspirin Attenuates the Bioactivation of and Platelet Response to Vicagrel in Mice. Issue 5 (November 2018) - Jia, Yu-Meng; Gu, Tong-Tong; Ji, Jin-Zi; Tai, Ting; Zhang, Meng-Ran; Huang, Bei-Bei; Zhou, Huan; Mi, Qiong-Yu; Xie, Hong-Guang
Abstract : Abstract: Vicagrel, a novel acetate analogue of clopidogrel, exerts more potent antiplatelet effect than clopidogrel in rodents. Relevant evidence indicated that aspirin and vicagrel are the drug substrate for carboxylesterase 2. Accordingly, it is deduced that concomitant use of aspirin could attenuate the bioactivation of and platelet response to vicagrel. To clarify whether there could be such an important drug–drug interaction, the differences in both the formation of vicagrel active metabolite H4 and the inhibition of adenosine diphosphate–induced platelet aggregation by vicagrel were measured and compared between mice treated with vicagrel alone or in combination with aspirin. The plasma H4 concentration was determined by liquid chromatography–tandem mass spectrometry, and the inhibition of platelet aggregation by vicagrel was assessed by whole-blood platelet aggregation. Compared with vicagrel (2.5 mg·kg −1 ) alone, concurrent use of aspirin (5, 10, or 20 mg·kg −1 ) significantly decreased systemic exposure of H4, an average of 38% and 41% decrease in Cmax and AUC0–∞ in mice when in combination with aspirin at 10 mg·kg −1, respectively. Furthermore, concomitant use of aspirin (10 mg·kg −1 ) and vicagrel (2.5 mg·kg −1 ) resulted in an average of 66% reduction in the inhibition of adenosine diphosphate–induced platelet aggregation by vicagrel. We conclude that aspirin significantly attenuates the formation of vicagrel active metabolite H4 and platelet response to vicagrel in mice, and that such an important drug–drug interaction would appear in clinical settings if vicagrel is taken with aspirin concomitantly when marketed in the future.